Peluang dan Hambatan Program Keluarga Berencana (KB) Krama Bali di Kelurahan Sesetan - Wahyuning Pertiwi, Putu Diah; Nugroho, Wahyu Budi; Kamajaya, Gede (JURNAL ILMIAH SOSIOLOGI: SOROT, 2023)
This study analyzes the opportunities and barriers to implementing the Balinese family planning program (KB Krama Bali) in Sesetan Village. Balinese family planning program is a family planning program based on Balinese local wisdom that states Balinese people have the right to have more than two children according to the Balinese naming, namely: Wayan, Made, Nyoman, and Ketut with the hope of creating a quality Balinese family. Balinese family planning program has intensified again through Bali Governor Instruction Number 1545 of 2019 with a statement that the names "Nyoman" and "Ketut" had started to become extinct, coupled with the presence of migrants. The method used in this research is a qualitative approach with a descriptive type. The theoretical analysis used as a scalpel in this study is the habitus theory and biological investment strategy from Pierre-Felix Bourdieu. The results of this study revealed that the implementation of the Balinese family planning program in the Sesetan Village was relatively small. Adhering to the patrilineal line, the culture of Balinese people indirectly obliges a family to have sons & the family's economic adequacy shows opportunities for the success of the Balinese family planning program. Consideration of factors that support life in forming a family is an obstacle in carrying out the Balinese family planning program. Other factors is the presence of migrants, in fact, did not provide a stimulus for Balinese people to implement the Balinese family planning program in Sesetan Village, considering that Sesetan Village is the area with the highest number of migrants in Denpasar City. The literacy of the Balinese people of Sesetan Village regarding quality compared to quantity in having offspring makes the concept of family planning that is considered appropriate for the peoples in Sesetan Village is the National Family Planning (KB) program.